Quantification of Climate Footprints of Vibrio vulnificus in Coastal Human Communities of the United States Gulf Coast - Jamal, Yusuf; Usmani, Moiz; Brumfield, Kyle D.; Singh, Komalpreet; Huq, Anwar; Nguyen, Thanh Huong; Colwell, Rita; Jutla, Antarpreet (Geohealth, 2024)
The incidence of vibriosis is rising globally with evidence of climate variability influencing environmental processes that support growth of pathogenic Vibrio spp. The waterborne pathogen, Vibrio vulnificus can invade wounds and has one of the highest case fatality rates in humans. The bacterium cannot be eradicated from the aquatic environment, hence climate driven environmental conditions enhancing growth and dissemination of V. vulnificus need to be understood to provide preemptive assessment of its presence and distribution in aquatic systems. To achieve this objective, satellite remote sensing was employed to quantify the association of sea surface temperature (SST) and chlorophyll‐a (chl‐a) in locations with reported V. vulnificus infections. Monthly analysis was done in two populated regions of the Gulf of Mexico—Tampa Bay, Florida, and Galveston Bay, Texas. Results indicate warm water, characterized by a 2‐month lag in SST, high concentration of phytoplankton, proxied for zooplankton using 1 month lagged chl‐a values, was statistically linked to higher odds of V. vulnificus infection in the human population. Identification of climate and ecological processes thresholds is concluded to be useful for development of an heuristic prediction system designed to determine risk of infection for coastal populations. Plain Language Summary Our study focused on Vibrio spp., a group of bacteria in warm, slightly salty water. One of these, Vibrio vulnificus, is especially dangerous and can cause severe illness with a high risk of death. The spread of this pathogen in humans is becoming more of a concern due to climate change. We aimed to understand what environmental conditions influence occurrence of the disease caused by this bacterium. The main factor linked to the rise of V. vulnificus is sea surface temperature (SST). However, other factors like chlorophyll also play a role. We used satellite data to monitor SST and chlorophyll levels and statistically associated this data with the number of people getting sick from V. vulnificus. Our findings indicate a pattern: when 2 months prior SST and 1‐month prior chlorophyll levels are higher than their monthly average, the chance of V. vulnificus infections is higher. By using this pattern, we aim to predict better when and where infections might happen, helping identify at‐risk areas and potentially stop outbreaks before they occur. Key Points Likelihood of Vibrio vulnificus infections is influenced by elevated Sea Surface Temperature and chlorophyll of previous months Sea Surface Temperature, chlorophyll, and V. vulnificus cases occurrence showed increasing trends during the study period Statistically significant difference was observed between overall chlorophyll levels and the levels recorded during increased cases of V. vulnificus